Development of Exposition Text Writing Teaching Materials With Genre Approach to Students of Grade X Vocational High School Brigjen Katamso Medan - Herson Ginting; M. Oky Gafari; Malan Lubis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aims of this study to find the validation conducted by the material expert validator on the development of the exposition text writing module. This research used development method by using population data of all student grade X vocational high school Brigjen Katamso Medan with total 92 students. The technique of collecting data by using by simple random sampling. . The results of the validation carried out by the material expert validator on the development of the exposition text writing module with the genre approach 89.11% with the category "Very Good". The results of the validation carried out by the design expert validator on the exposition text writing module overall average value of 90.80% with the category "Very Good". The teacher's assessment of the exposition text writing module with the genre approach for grade X students obtained an average value of 80.70% in the "good" category